The Use of Interactive Liveworksheet for Listening Skills in Grade XI SMA Negeri 1 Tumpang - Aisyah Aulia Mahaputri Rosadi; Sri Prameswari Indriwardhani; Eliska Gawlikova (International Journal of Pedagogical Language, Literature, and Cultural Studies (i-Plural), 2025)
This study aims to describe the implementation and student responses to the use of web-based Interactive worksheet called Liveworksheet as a tool for training German Listening skills in grade XI students at SMA Negeri 1 Tumpang. The Liveworksheet used in this research focuses on the theme Kennenlernen with the sub themes sich vorstellen and Zahlen. Using a descriptive qualitative research method, the study involved 30 students from class XI L during the odd semester in 2024 academic year as its data source. Observations revealed that interactive Liveworksheet serves as an effective supplementary teaching material for practicing German Listening skills. Furthermore, student responses indicated that Liveworksheet offers a new and exciting task experience. Despite its advantages, the findings highlight the need for guidance and assistance from teachers. Continuous support is needed to ensure students can utilize the Interactive worksheet effectively during the learning process and overcome difficulties during practicing with Liveworksheet.